On the Effects of Saturation Terms on A SEIR Epidemic Model with Infected and Susceptible Compartments - Mutairu Kayode Kolawole; Olakunle L. Moshood; Kehinde A. Bashiru; Adedapo I. Alaje; Amos O. Popoola; Hammed O. Adekunle (Jambura Journal of Mathematics, 2023)
The importance of the saturation term in an SEIR (Susceptible, Exposed, Infected, and Recovered) epidemic model was examined in this article. To estimate the basic reproduction number (R0), examine the stabilities and run numerical simulations on the model, the next generation matrix, the Lyapunov function and Runge-Kutta techniques were used. The numerical simulation results reveal that, the saturation term has a significant influence in the model’s susceptible and infected compartments. However, as demonstrated by the simulation results, saturation term has a greater influence on vulnerable people than on infected people. As a result, greater sensitization programs through seminars, media, and awareness will be more beneficial to the vulnerable class than the afflicted class during disease eradication.